A cost-effective dual reporter system in Nicotiana benthamiana - Zhang, Zeru; Yan, Shuangle; Li, Fuqi; Rao, Zhijuan; Fan, Fahong; Ren, Haibin; Qu, Yanlin; Yang, Ke; Ma, Chuanyu; Zhuang, Chen; Lin, Chentao; Qu, Gaoping (Frontiers in Plant Science, 2026)
Dual reporter assay has been widely used for quantification of gene expression in various model systems. However, the assay is dependent on commercial kits, which may be inhibitory for many low-budget academic laboratories or high throughput screening. Here, we systematically characterized seven commonly used or potential reporters, and identified NanoLuc-GFP pair as the optimal kit-independent and accurate dual reporter in Nicotiana benthamiana. The NanoLuc-GFP system exhibited high stability, which can largely reduce the interference caused by biological variability and dramatic environmental fluctuations. Furthermore, it exhibits greater sensitivity compared to the conventional FLuc/RLuc system commercially available.